The Edinburgh companion to shari'ah governance in Islamic finance - Ali, Syed Nazim, 1949-; Tariq, Wijdan; Al-Quradaghi, Bahnaz (Edinburgh University Press, 2020)
Written by a group of prominent shari'ah scholars, academics and practitioners in the field of Islamic finance, this book contains 17 in-depth case studies of shari'ah governance practices and experiences as well as critical analysis of these practices. It serves as a standalone comprehensive reference work on shari'ah governance, containing an overview of its Islamic legal foundations, its evolution and development over the years, current practices and debates on shari'ah governance standards and future prospects for shari'ah governance in the global Islamic finance market.